A needle in a haystack: Mesozoic origin of parasitism in Strepsiptera revealed by first definite Cretaceous primary larva (Insecta) - Hans Pohl; Jan Batelka; Jakub Prokop; Patrick Müller; Margarita I. Yavorskaya; Rolf G. Beutel (PeerJ, 2018)
Twisted winged insects (Strepsiptera) are a highly specialized small order of parasitic insects. Whether parasitism developed at an early or late stage in the evolution of the group was unknown. Here we record and describe the first definite Mesozoic strepsipteran primary larva embedded in Burmese amber (∼99 million years ago). This extends the origin of parasitism back by at least ∼50 million years, and reveals that this specialized life style has evolved in the Mesozoic or even earlier in the group. The extremely small first instar displays all diagnostic characters of strepsipteran immatures of this stage and is nearly identical with those of Mengenillidae, one of the most “ancestral” extant strepsipteran taxa. This demonstrates a remarkable evolutionary stasis over  100 million years. The new finding strongly weakens the case of small larvae embedded in Cretaceous amber interpreted as strepsipteran immatures. They differ in many structural features from extant strepsipteran primary larvae and are very likely parasitic beetle larvae.